Social Competence of School Principals in Improving the Quality of Education at Kutai Kartanegara Vocational High School - Warman Warman; Wilis Haryo Sumantri; Rahmat Soe’oed (PT ARRUS Intelektual Indonesia, 2024)
This research aims to describe the social competence of school principals in planning, and implementing, obstacles and solutions for improving the quality of education at Kutai Kartanegara Vocational High School. This research uses a descriptive qualitative approach. Data collection in the research involved three informants, namely the principal, deputy principal, and teacher. The data collection methods used were observation, interviews, and documentation. The data analysis process is carried out through the stages of reduction, presentation, and drawing conclusions. The results of this research show that: 1) The social competence of school principals in planning to improve the quality of education is the principal's ability to lead the school community, especially teachers, starting from an integrated approach which is divided into three, namely communication, collaboration and cooperation with internal and external parties. external school; 2) The implementation of the school principal's social competence in improving the quality of education is carried out by the principal through implementation and supervision of current and future programs as well as the principal providing training and modules for teachers that are relevant to the programs occurring in the field; 3) Obstacles to the social competence of school principals in improving the quality of education, namely financial limitations, discipline and priority scale; 4) The solution to the social competence of school principals in overcoming financial limitations is to carry out intensive communication and approaches, overcome disciplinary obstacles by carrying out internal and external collaboration, while the solution to priority scale obstacles is to provide training and development, as well as a long-term approach to programs implemented in school.